Confirmatory assays are essential when using molecular testing for Neisseria gonorrhoeae in low-prevalence settings: insights from the third National Survey of Sexual Attitudes and Lifestyles (Natsal-3). (15th December 2014) - Field, Nigel; Clifton, Soazig; Alexander, Sarah; Ison, Catherine A; Hughes, Gwenda; Beddows, Simon; Tanton, Clare; Soldan, Kate; Coelho da Silva, Filomeno; Mercer, Catherine H; Wellings, Kaye; Johnson, Anne M; et al.
Abstract : Objectives: To investigate the occurrence of unconfirmed positive gonorrhoea results when using molecular testing within a large population-based survey. Design, setting and participants: Between 2010 and 2012, we did a probability sample survey of 15 162 men and women aged 16–74 years in Britain. Urine from participants aged 16–44 years reporting ≥1 lifetime sexual partner was tested for Neisseria gonorrhoeae and Chlamydia trachomatis using the Aptima Combo 2 (AC2) assay, with positive or equivocal results confirmed with molecular assays using different nucleic acid targets. Results: A total of 4550 participants aged 16–44 years had urine test results (1885 men; 2665 women). For gonorrhoea, 18 samples initially tested positive and eight were equivocal. Only five out of 26 confirmed, giving a positive predictive value (PPV) for the initial testing of 19% (95% CI 4% to 34%). Most (86% (18/21)) participants with unconfirmed positive results for gonorrhoea reported zero or one sexual partner without condoms in the past year and none had chlamydia co-infection, whereas all five with confirmed gonorrhoea reported at least two recent sexual partners without condoms, and four had chlamydia co-infection . The weighted prevalence for gonorrhoea positivity fell from 0.4% (0.3% to 0.7%) after initial screening to <0.1% (0.0% to 0.1%) after confirmatory testing. By comparison, 103 samples tested positive or equivocal for chlamydia and 98 were confirmed (PPV=95% (91% to 99%)). Conclusions: We highlight the low PPV for gonorrhoea of an unconfirmed reactive test when deploying molecular testing in a low-prevalence population. Failure to undertake confirmatory testing in low-prevalence settings may lead to inappropriate diagnoses, unnecessary treatment and overestimation of population prevalence.